2022
DOI: 10.5551/jat.59642
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Stroke Outcome Extracted from Multivariate Linear Discriminant Analysis or Neural Network Analysis

Abstract: Aim: The prediction of functional outcome is essential in the management of acute ischemic stroke patients. We aimed to explore the various prognostic factors with multivariate linear discriminant analysis or neural network analysis and evaluate the associations between candidate factors, baseline characteristics, and outcome. Methods: Acute ischemic stroke patients ( n =1,916) with premorbid modified Rankin Scale (mRS) scores of 0–2 were analyzed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…The studies that applied GNRI to stroke patients have been carried out (since 2016) in Far Eastern Asian countries [ 7 , 14 , 15 , 16 , 27 , 29 , 30 , 31 , 32 , 34 , 37 , 42 , 43 , 45 , 46 , 47 , 48 , 50 , 53 , 54 , 55 , 57 , 58 , 63 , 64 , 66 , 68 , 70 , 71 ], as shown in Table 1 . A significant risk of malnutrition has usually been defined by a GNRI score <92, with some exceptions (for example, a score <98 [ 7 ] or <100 [ 27 ]).…”
Section: Nutritional Screening Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies that applied GNRI to stroke patients have been carried out (since 2016) in Far Eastern Asian countries [ 7 , 14 , 15 , 16 , 27 , 29 , 30 , 31 , 32 , 34 , 37 , 42 , 43 , 45 , 46 , 47 , 48 , 50 , 53 , 54 , 55 , 57 , 58 , 63 , 64 , 66 , 68 , 70 , 71 ], as shown in Table 1 . A significant risk of malnutrition has usually been defined by a GNRI score <92, with some exceptions (for example, a score <98 [ 7 ] or <100 [ 27 ]).…”
Section: Nutritional Screening Toolsmentioning
confidence: 99%
“…All the studies applying the CONUT tool to stroke patients were carried out (since 2018) in Far Eastern Countries, with the exception of one from Spain [ 14 , 15 , 17 , 20 , 22 , 23 , 25 , 26 , 30 , 33 , 34 , 36 , 40 , 41 , 44 , 45 , 46 , 56 , 60 , 61 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ], as reported in Table 1 . Stroke patients were classified according to the original four, but also in three (normal, light, and moderate/severe risk) or in two (absence or presence of risk) categories; a CONUT score ≥5 was commonly defined as the cut-off for a significant risk of malnutrition, but in two papers the cut-off was ≥2 [ 72 ] or ≥4 [ 23 ], respectively.…”
Section: Nutritional Screening Toolsmentioning
confidence: 99%
“…In addition, serum ALP levels are a good predictor of all-cause mortality and functional outcomes of acute stroke 10,11) . We previously reported that serum ALP levels extracted using a neural network analysis were independently associated with poor stroke outcomes at 3 months 12) . Although the association between increased ALP levels and stroke outcomes is not completely clear, we speculated that the effect of PAD is mediated by vascular calcification.…”
Section: Study Populationmentioning
confidence: 99%
“…The prevalence of premorbid malnutrition was around 33% to 34.3% for acute ischemic stroke (AIS) patients at admission [ 3 , 4 ]. Recent evidence demonstrated that malnutrition at admission was related to unfavorable stroke outcomes in AIS patients, such as increased mortality and poor neurological function at 90 days of onset [ 5 , 6 , 7 ]. The impact of malnutrition on prognosis after AIS exists not only in the acute stage but also in the chronic phase [ 7 ].…”
Section: Introductionmentioning
confidence: 99%